(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This research looks into ‘influence of financial inclusion on women's’ workforce participation in India. Current study works at the grassroots level, investigating the function of labor force participation in promoting sustainability and growth. It investigates whether women's labor-force involvement leads to financial inclusion, and therefore to development. It also looks into how digitalization might help promote financial liberty. This review article synthesizes expert perspectives & emphasis relevance of ‘financial inclusion in achieving’ the objective of a developed nation by 2047. The study stated that digitization, women's labor engagement, & ‘financial inclusion’ are critical in moving India to developed nation status. Digitalization promotes economic growths by increasing efficiency and transparency. Increased labor engagement, particularly between women & underprivileged areas, guarantees that benefits of economic progress were dispersed fairly, resulting in a more inclusive and sustainable development model.